Mythological analysis of six stories of Kurdish chronology rituals among the Sanjābi, Kalhor and Gorān tribes - zahra jamshidi (پژوهشنامه ادبیات کردی)
The Kurdish oral chronology of Kermanshah is one of the oldest manifestations of the culture and civilization of the people, whose special stories and rituals are linked with the ancient myths and religions of Iran. In the present study, we have investigated the Kurdish chronology and its rituals among the: Sanjābi, Kalhor and Gorān clans using a descriptive, analytical and field method. According to research, Kurdish oral chronology is heavily influenced by fetishism, Mithraism, Zoroastrianism and common beliefs in Mesopotamia. In this chronology, the year has three hundred and sixty days and four seasons, but due to the importance of the spring season for rural people, most rituals are specific to this season; Especially the beginning of spring, which coincides with the fifteenth of Bahman of the Jalali calendar. The ritual of cooking "pa peg" on the first day of spring in connection with fetishism and farrah, belief in the mother of the first spring related to the era of matrilineal descent, the story of the kore seyāy, the reproduction of the martyred vegetable god, the story of Shave Gā Huyl in connection with Mehri beliefs and the story of Kale vā, is a repetition of the fight of vāye nik and vāye bad.